Pharmacokinetics of nebulized colistin methanesulfonate in critically ill patients. (1st June 2017) - Boisson, Matthieu; Grégoire, Nicolas; Cormier, Marielle; Gobin, Patrice; Marchand, Sandrine; Couet, William; Mimoz, Olivier
Abstract: Objectives: Optimal dosing for nebulized colistin methanesulfonate (CMS), the prodrug of colistin, is unknown. We describe the pulmonary and systemic pharmacokinetics of CMS and colistin following nebulization of 0.5 million IU (MIU) of CMS in ventilated patients. Methods: Twelve critically ill patients received 0.5 MIU of CMS administered every 8 h as 30 min nebulizations. Blood samples were collected immediately before and until 8 h after first nebulization; mini-bronchoalveolar lavage (mini-BAL) was performed at 1 and 5 h or 3 and 8 h (six patients each) post-dose. Pharmacokinetic analysis was performed for CMS and colistin plasma concentrations using a non-compartmental method. ClinicalTrials.gov: NCT01060891. Results: After nebulization, CMS concentrations in epithelial lining fluid (ELF) were much higher (100- to 1000-fold) than those in plasma. Concentrations of colistin in ELF should be considered with caution because when <6 mg/L in BAL, colistin bound to mini-BAL devices. Nevertheless, CMS and colistin concentrations in ELF were much lower than expected from previous results with a 2 MIU dose. From CMS plasma pharmacokinetics it was shown that CMS systemic bioavailability was only slightly decreased for the 0.5 MIU dose compared with 2 MIU. Conclusions: This study shows that CMS concentrations were much higher (100- to 1000-fold) in ELF than in plasma after a 0.5 MIU aerosol of CMS, but much lower (10-fold) than expected from previous results with a 2 MIU dose. Therefore, until new pharmacokinetic and pharmacodynamic assessments of the treatment of ventilator-associated pneumonia with nebulized CMS are performed, the 2 MIU dose should be preferred to the 0.5 MIU dose.